PENGGUNAAN APLIKASI KASIR PINTAR DALAM PENCATATAN KEUANGAN (STUDI KASUS UMKM POKLAHSAR WISNA FRESH) - Pratiwi Kartika Dewi; Silvya Eka Safitry; Ardyan Firdausi Mustoffa (Jurnal Abdimas Sangkabira, 2021)
Research in this community service program is carried out to help owners solve problems, namely the entry and exit of sold products, recording inventory of ready-to-sell products, and the amount of profit earned from sales. So far, the owner's recording is still very simple and doesn't even keep records at all. Taking this topic aims to help make it easier for the owner as a business actor to control the sales of their products and to help the owner to make it easier to find out the amount of profit earned from sales. In using the Smart Cashier application, it can make it easier to check the amount of inventory, find out the amount of production, the number of products sold, and the profit earned from sales. The results of using the Smart Cashier application help the owner check the amount of inventory, find out the number of products sold, the profit earned from sales, and print sales receipts